We who have no gods : a novel - Anderson, Liza (Ballantine Books, 2026)
"Vic Wood knows her priorities: scrape by on her restaurant wages, take care of her younger brother Henry, and forget their mother ever existed. But Vic's careful life crumbles when Henry reveals that their long-missing mother belonged to the Acheron Order - a secret society of witches tasked with keeping the dead at bay. What's worse, Henry inherited their mother's magical abilities while Vic did not, and Henry has been chosen as the Order's newest recruit. Determined to keep him safe, Vic accompanies Henry to the isolated woods in upstate New York that play host to the sprawling and eerie Avalon Castle. When she joins the academy despite lacking powers of her own, she risks not only the Order's wrath, but also her brother's. And then there is Xan, the head Sentinel - imposing, ruthless, and frustrating - in charge of protecting Avalon. He makes no secret that he wants Vic to leave. As she makes both enemies and allies in this mysterious realm, Vic becomes caught between the dark forces at play, with her mother at the heart of it all. What's stranger is Vic begins to be affected by the academy - and Xan - in ways she can't quite understand. But with war between witches threatening the fabric of reality, Vic must decide whether to risk her heart and life for a world where power is everything"-- Provided by publisher.